The Writer's advisor - Alkire, Leland G.; Westerman, Cheryl I. (Gale Research, 1985)
"A guide to books and articles about writing novels, short stories, poetry, dramatic scripts, screenplays, magazine articles, biographies, technical articles and books, as well as a guide to information about literary agents, marketing, and a wide range of legal and business materials of interest to full and part-time writers."